1991
DOI: 10.1007/bf00021244
|View full text |Cite
|
Sign up to set email alerts
|

Sources of heat tolerance amongst potato cultivars, breeding lines, and Solanum species

Abstract: This study assessed 46 potato cultivars, breeding lines and Solanum spp. for heat-tolerance using short-term growth rates and carbon assimilation measurements of young in-vitro-derived plants. Plants of the 46 clones and species were transferred from greenhouse conditions to controlled conditions set at 33/25° C day/night with 12 h photosynthetic photon flux density (PPFD) at 430--450/xmol m-2s -1 and an 8 h daylength extension (6/xmol m-2s-1), to inhibit tuberization. Twenty eight accessions were also grown i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…Varieties such as Tomasa Condemayta, and 396244.17 are good candidates for heat tolerance. These results are consistent with previous reports where Nowak and Colborne (1989) confirmed CIP breeding line LT2 as a heat resistant clone, Midmore and Prange (1991) noted that AVRDC 1287.19 produced more dry weight in the hot chamber than the cool chamber, and Carli et al (2009) confirmed Reiche, Tacna, and CIP 397077.16 as well-adapted clones for hot summer conditions of Central Asia.…”
Section: Resultssupporting
confidence: 92%
“…Varieties such as Tomasa Condemayta, and 396244.17 are good candidates for heat tolerance. These results are consistent with previous reports where Nowak and Colborne (1989) confirmed CIP breeding line LT2 as a heat resistant clone, Midmore and Prange (1991) noted that AVRDC 1287.19 produced more dry weight in the hot chamber than the cool chamber, and Carli et al (2009) confirmed Reiche, Tacna, and CIP 397077.16 as well-adapted clones for hot summer conditions of Central Asia.…”
Section: Resultssupporting
confidence: 92%
“…Whilst cultivated potato is generally a cool climate crop, there is significant variation in response to heat stress between cultivars (Levy, ; Levy et al ., ; Marinus and Bodlaender, ; Mendoza and Estrada, ; Menzel, ; Midmore and Prange, ), in land races and wild potato species (Hetherington et al ., ; Mendoza and Estrada, ; Reynolds and Ewing, ) and in progeny clones from heat‐tolerant parents (Haynes and Haynes, ; Mendoza and Estrada, ; Morpurgo et al ., ; Veilleux et al ., ). Despite reported variation, we are unaware of any reports that identify QTL for heat tolerance in potato.…”
Section: Introductionmentioning
confidence: 99%
“…There are two prerequisites for success of a breeding program aimed to develop heat-tolerant cultivars: choosing the most appropriate parents and using a reliable screening method in early generations (Hijmans, 2003;Levy and Veilleux, 2007). Previous studies indicated that it is possible to find sources for heat tolerance among potato varieties, breeding lines, and wild Solanum species (Gautney and Haynes, 1983;Levy, 1986;Levy et al, 1991;Reynolds and Ewing, 1989;Midmore and Prange, 1991;Tai et al, 1994), and it is also possible to breed heat-tolerant potato varieties using conventional breeding (Susnoschi et al, 1987;Levy et al, 1991;Haynes et al, 1992;Veilleux et al, 1997;Levy et al, 2001) and mutations (Das et al, 2000). Using a reliable selection method is crucial for success in a breeding program aimed at developing heattolerant potato varieties (Sattelmacher, 1983;Nowak and Colborne, 1989;Reynolds and Ewing, 1989;Veilleux et al, 1997;Levy and Veilleux, 2007).…”
Section: Introductionmentioning
confidence: 99%